Immediate vs. Delayed Pushing. Issue 2 (March 2019) - Simpson, Kathleen Rice
Abstract : When a woman in labor reaches 10 cm cervical dilation, she can either begin pushing immediately or wait until she feels the urge to push. As evidence continues to evolve about advantages and disadvantages of each option, nurses must keep up-to-date and be ready to have a discussion as part of the clinical team that includes the woman as a full partner and covers the important considerations. A recent study about immediate or delayed pushing for nulliparous women with epidural analgesia is reviewed.